ASD: emotions and behavioural-based interventions through social sensor networks. (2018) - Faustin, Uwizeyimana; Kovalan, A.; Kannan, Rajkumar
In India, nowadays one per 88 children is born with autism spectrum disorder (ASD) contrary to a ratio of one per 110 children few years back. In this paper, we propose a social sensor network for individuals with ASD to offer medical promotions as intervention and first aid. They should be in care and medical surveillances. We are monitoring enjoyment, frustration, boredom, and stress by using body-worn sensors and video streaming. This sensor collects the information from the human body and transmits it to their smart phones then to the external server. We introduce an algorithm named as spectrum clustering algorithm (SCA) which clusters people based on activities of the child. Communication is provided between the clusters of people by using context recommendation algorithm. We use prerogative response algorithm (PRA) for load balancing on server while processing the requests. Our processes are simulated using Omnet++ simulator and provide effective results.